Pinocembrin Decreases Ventricular Fibrillation Susceptibility in a Rat Model of Depression - Ye, Tianxin; Zhang, Cui; Wu, Gang; Wan, Weiguo; Guo, Yan; Fo, Yuhong; Chen, Xiuhuan; Liu, Xin; Ran, Qian; Liang, Jinjun; Shi, Shaobo; Yang, Bo (Frontiers in Pharmacology, 2020)
Background: Depression is associated with the increased risk of mortality and morbidity, and is an independent risk factors for many cardiovascular diseases. Depression may promote cardiac arrhythmias, but little is known about the mechanisms. Pinocembrin mitigated depressive-like behaviors and exhibited cardioprotective effects in several models; however, whether pinocembrin benefits ventricular arrhythmias (VAs) in depression models has not been elucidated. Thus, this study was to evaluate the effects of pinocembrin on ventricular fibrillation (VF) susceptibility in rat models of depression. Methods: Male Sprague-Dawley (SD) rats were randomly assigned into CTL (control), CTP (CTL + pinocembrin), MDD (major depressive disorder) and MDP (MDD + pinocembrin) groups, respectively. Depressive-like behaviors, ventricular electrophysiological parameters, electrocardiogram parameters, heart rate variability (HRV), ventricular histology, serum norepinephrine (NE), tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) were detected. Protein levels in left ventricle (LV) were measured by Western blot assays. Results: Compared with the MDD group, pinocembrin significantly mitigated depressive-like behaviors, prolonged ventricular effective refractory period (ERP), action potential duration (APD), QT and corrected QT (QTc) interval, improved heart rate variability (HRV), decreased Tpeak–Tend interval, VF inducibility rate, ventricular fibrosis, ventricular positive nerve densities and protein expression of tyrosine hydroxylase (TH) and growth associated protein-43 (GAP43), reduced serum NE, TNF-α, IL-1β concentrations, and the expression levels of p-IκBα and p-p65, and increased the protein expression of Cx43, Cav1.2, and Kv.4.2 in the MDP group. Conclusions: Pinocembrin attenuates ventricular electrical remodeling, autonomic remodeling, and ion-channel remodeling, lowers ventricular fibrosis, and suppresses depression-induced inflammatory responses, providing new insights in pinocembrin and VAs in depressed patients.